Pengembangan Management Energi Dengan Solar Panel Yang di Terapkan Pada Tempat Sampah - Aulia Rahmah; Agus Triyono; Karyo Budi Utomo (JURNAL VOKASI TEKNIK, 2026)
This study designs a solar panel to support the operation of an automatic waste segregation system. The primary focus is to develop an efficient and reliable solar panel. The methods include literature review, energy requirement analysis, design, and performance testing of the solar panel. The results indicate that the developed solar panel effectively supports the system's operation. Developing a reliable and efficient solar panel is essential for a self-sustaining waste management system and provides additional insights into renewable energy usage in waste management.